Long-Term Pre-Conception Exposure to Local Violence and Infant Health - Eunsik Chang; Sandra Orozco-Aleman; María Padilla-Romo (Institute of Labor Economics (IZA), 2024)
This paper studies the effects of mothers' long-term pre-conception exposure to local violence on birth outcomes. Using administrative data from Mexico and two different empirical strategies, our results indicate that mothers' long-term exposure to local violence prior to conception has detrimental effects on infant health at birth. The results suggest that loss of women's human capital and deterioration of mental health are potential underlying mechanisms behind the adverse effects, highlighting intergenerational consequences of exposure to local violence. Our findings shed light on the welfare implications of local violence that are not captured in in-utero exposure to violence.
Keywords: J13; I12; 330; birth outcomes; local violence; pre-conception; maternal stress